2020
DOI: 10.3126/nmcj.v22i3.32624
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Factors Associated with Dropout for Pentavalent Vaccine in Tertiary Care Hospital of Kathmandu, Nepal

Abstract: Immunization is one of the most cost-effective public health measures as it has helped in huge reduction of disease, disability and death from different infectious diseases in children by protecting them from vaccine preventable diseases. The current study aimed to study factors associated with dropout for pentavalent vaccine in tertiary care hospital of Kathmandu. A longitudinal observational study using purposive sampling technique was conducted among 196 infants. The information was obtained using self-cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
2
1
Order By: Relevance
“…Comparatively, our study’s findings were lower than those of research conducted in Nepal (28.5%) 61 and India (26.1%). 62 The study setting, time gap and the sample size across the studies of may be contributing factors to this variation.…”
Section: Discussioncontrasting
confidence: 99%
“…Comparatively, our study’s findings were lower than those of research conducted in Nepal (28.5%) 61 and India (26.1%). 62 The study setting, time gap and the sample size across the studies of may be contributing factors to this variation.…”
Section: Discussioncontrasting
confidence: 99%
“…However, when compared to a previous study carried out in the pre-pandemic period at the same clinic, a lower dropout rate (10% vs 29%) was seen. 7 Several global reviews and country-level studies had reported a decline in the number of administered vaccine doses. Moreover, the largest decline (57%) was observed in the South-East Asia region in the number of administered doses of diphtheria-pertussistetanus-containing vaccine (DTP3) and Measles vaccine (MR1) in the first half of 2020.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated sample size was calculated assuming a 29% drop-out rate for the third dose of Pentavalent vaccine based on a study carried out in our clinic. 7 Within 95% confidence intervals and a 7% margin of error, the minimum sample size was calculated to be 161 infants. Infants who received BCG from 1 st April 2021 to 31 st July 2021 at the clinic with a minimum of two visits over a one-year period were included in the study.…”
Section: Introductionmentioning
confidence: 99%